BORON REMOVAL FROM SURFACE WATER USING A FIXED-BED COLUMN WITH AMBERLITE IRA 743: DYNAMIC STUDY AND LOGISTIC MODELING - Avendaño Cáceres, Edgardo (2025)
The objective of this study was to determine the column capacity and adsorption isotherm, adjust and analyze breakthrough curves, and determine the parameters of the logistic equation for three fixed bed models (Bohart-Adams, Thomas, and Yoon-Nelson). Amberlite IRA 743 resin was used and the column operated at 3, 7, and 11 mL min⁻¹. The logistic equation was employed to adjust breakthrough curves and determine the parameters for the three fixed bed models. Column capacity was based on breakthrough time (tb), total capacity (tt), and usable capacity (tu). Boron analysis was performed by visible spectrophotometry using Azomethine H. The Langmuir model showed better fit to experimental data with qmáx = 11,97 mg g⁻¹ and b = 0,02 L mg⁻¹. Experimental data from breakthrough curves for 3, 7, and 11 mL min⁻¹ were fitted to the logistic equation obtaining R² = 0,985, 0,997, and 0,999, respectively. In the determination of column capacity, it was found that tu/tt (fraction of bed capacity used up to the breakthrough point) for flow rates of 3, 7, and 11 mL min⁻¹ were 0,67, 0,39, and 0,25, respectively. Results demonstrated that the Langmuir model showed better fit to experimental data, and breakthrough curves and column capacity showed that low flow rates optimize contact and use of the adsorbent bed.